A review on slip boundary conditions at the nanoscale: recent development and applications - Wang, Ruifei; Chai, Jin; Luo, Bobo; Liu, Xiong; Zhang, Jianting; Wu, Min; Wei, Mingdan; Ma, Zhuanyue (Beilstein Journal of Nanotechnology, 2021)
The slip boundary condition for nanoflows is a key component of nanohydrodynamics theory, and can play a significant role in the design and fabrication of nanofluidic devices. In this review, focused on the slip boundary conditions for nanoconfined liquid flows, we firstly summarize some basic concepts about slip length including its definition and categories. Then, the effects of different interfacial properties on slip length are analyzed. On strong hydrophilic surfaces, a negative slip length exists and varies with the external driving force. In addition, depending on whether there is a true slip length, the amplitude of surface roughness has different influences on the effective slip length. The composition of surface textures, including isotropic and anisotropic textures, can also affect the effective slip length. Finally, potential applications of nanofluidics with a tunable slip length are discussed and future directions related to slip boundary conditions for nanoscale flow systems are addressed.
Keywords: boundary condition; interfacial properties; nanofluidics; slip length; unconventional reservoirs